Powered knee orthosis for human gait rehabilitation: first advances - Felix, Paulo (2017)
This paper presents a new system for a powered knee orthosis, that was designed to assist and improve the gait function of patients with gait pathologies. The system contains the orthotic device (embedded with sensors for angle and user-orthosis interaction torque measurements, and an electric actuator) and wearable sensors (inertial measurement unit, force sensitive resistors, and electromyography sensors), which allows the generation of smart rehabilitation tools and several motion assistive techniques. The main goal is to present a conceptual overview and functional description of the system and use scenarios of each component. The attachment mechanism of the orthosis to the limb is also highlighted, being composed of a straps system fixed in the mechanical links of the joint. It was noticed that users with distinct lower-limb morphologies can presents difficulties wearing the orthosis, since the device needs constant adjust to align the mechanical and human joints. The system was validated in ground-level walking on healthy subjects, with emphasis on the impact of the device in the user. The subjects reported that the orthosis is comfortable to use, easy to wear, and no issues were raised regarding the aesthetics of the device. Only the weight was assimilated as a possible hindrance (compensated in the future). Future challenges involve the inclusion of an ankle joint in the system and the use of the proposed tool in rehabilitation.